The Role Of Islamic Leadership On Employee Performance: The Mediation Role Of Employee Engagement - Azizah, Alissa (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Leadership has an important role in improving employee performance in a com-pany. As is the case with the Islamic leadership style that has existed since the time of the Prophet with the four known characteristics, namely Shidiq, Amanah, Fato-nah, and Tabligh. Testing the direct and indirect influence of Islamic leadership traits on employee performance is the aim of this research, by using employee involvement as a mediating variable. Explanatory research with primary data at the Tritya Eye Clinic collected through an online Google Form questionnaire. The research results show that the nature of Islamic leadership has a direct influence on employee performance. And employee involvement is only able to mediate the nature of Islamic leadership (shidiq) on employee performance.